Pastplay : Teaching and Learning History with Technology - Kee, Kevin B. (Kevin Bradley), 1969- (Digital humanities (Ann Arbor, Mich.), 2014)
In the field of history, the Web and other technologies have become important tools in research and teaching of the past. Yet the use of these tools is limited--many historians and history educators have resisted adopting them because they fail to see how digital tools supplement and even improve upon conventional tools (such as books). In Pastplay, a collection of essays by leading history and humanities researchers and teachers, editor Kevin Kee works to address these concerns head-on. How should we use technology? Playfully, Kee contends. Why? Because doing so helps us think about the past in new ways; through the act of creating technologies, our understanding of the past is re-imagined and developed. From the insights of numerous scholars and teachers, Pastplay argues that we should play with technology in history because doing so enables us to see the past in new ways by helping us understand how history is created; honoring the roots of research, teaching, and technology development; requiring us to model our thoughts; and then allowing us to build our own understanding.